Copper homeostasis; A rapier between mycobacteria and macrophages - Di Hu; Zisha Yang; Jun‐ai Zhang; Ganbin Liu; Jiang Pi; Junfa Xu; Yan Wang; Yi Zhao (FASEB BioAdvances)
Abstract Copper is a vital trace element crucial for mediating interactions between Mycobacterium and macrophages. Within these immune cells, copper modulates oxidative stress responses and signaling pathways, enhancing macrophage immune functions and facilitating Mycobacterium clearance. Conversely, copper may promote Mycobacterium escape from macrophages through various mechanisms: inhibiting macrophage activity, diminishing phagocytic and bactericidal capacities, and supporting Mycobacterium survival and proliferation. This paradox has intensified research focus on the regulatory role of copper in immune cell–pathogen interactions. Interactions among metal ions can affect Mycobacterium concentration, distribution, and activity within an organism. In this review, we have elucidated the role of copper in these interactions, focusing on the mechanisms by which this metal influences both the immune defense mechanisms of macrophages and the survival strategies of Mycobacterium. The findings suggest that manipulating copper levels could enhance macrophage bactericidal functions and potentially limit Mycobacterium resistance. Therefore, elucidating the regulatory role of copper is pivotal for advancing our understanding of metal homeostasis in immune cell–pathogen dynamics and TB pathogenesis. Furthermore, we recommend further investigation into the role of copper in TB pathogenesis to advance tuberculosis diagnosis and treatment and gain comprehensive insights into metal homeostasis in infectious disease contexts.